2018
DOI: 10.1590/1678-5150-pvb-5528
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and molecular findings of avian avulavirus type 1 outbreak in pigeons (Columba livia) of southern Brazil

Abstract: The Newcastle disease, caused by avian avulavirus type 1 strains (APMV-1) is an important avian disease involved into high rates of mortality and economic losses. Several outbreaks have been reported over the last 30 years in Columbiformes in different parts of the world, caused by a adapted variant strain of AAvV-1, called pigeon paramyxovirus type 1 (PPMV-1). A high mortality associated with an outbreak was analyzed in free-living pigeons (Columba livia) in a public square in Porto Alegre in Southern Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Natural infection of pigeons and doves with viruses of genotype VI.2.1 (nucleotide identity of >95%) was reported to induce Additionally, comparable nervous signs and mortality rates were observed on birds from which similar VI.2.1 sequences (> 95%) were recovered ( 56 , 63 , 64 ). Likewise, similar nervous signs were reported in pigeons infected with less similar isolates of genotype VI.2.1 ( 54 , 65 ) and genotype VI.2.2.2.2 ( 66 ). Inconsistent clinical signs were reported after the experimental infection of pigeons with viruses of genotype VI.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Natural infection of pigeons and doves with viruses of genotype VI.2.1 (nucleotide identity of >95%) was reported to induce Additionally, comparable nervous signs and mortality rates were observed on birds from which similar VI.2.1 sequences (> 95%) were recovered ( 56 , 63 , 64 ). Likewise, similar nervous signs were reported in pigeons infected with less similar isolates of genotype VI.2.1 ( 54 , 65 ) and genotype VI.2.2.2.2 ( 66 ). Inconsistent clinical signs were reported after the experimental infection of pigeons with viruses of genotype VI.…”
Section: Discussionsupporting
confidence: 81%
“…RT-PCR, followed by sequencing of the F gene, has been widely used to detect virulence and to connect AOAVs recovered from different outbreaks ( 65 ). The present study's genotyping RT-PCR failed to detect AOAV1 in samples from 2 out of the eight pigeon flocks.…”
Section: Discussionmentioning
confidence: 99%
“…Our phylogenetic analysis, using 62 complete NDV genome sequences available at GenBank, revealed that the NDV/pigeon/PE-Brazil/MP003/2018 belongs to genotype VI.2.1.2. This virus was closely related to other viruses isolated from pigeons in Argentina, Rio Grande do Sul (southern Brazil) and São Paulo in 2019 (southeastern Brazil) [ 32 , 33 , 35 ]. Since the genotype VI of NDV is frequently found in pigeons, this strain is commonly named Pigeon Paramyxovirus 1 (PPMV-1) [ 27 ].…”
Section: Discussionsupporting
confidence: 52%
“…The pigeons in this study presented neurological signs and lesions commonly observed in other Columbiformes infected by NDV [ 32 , 33 , 34 , 35 ]. The gross findings were nonspecific, which is consistent with previous reports from the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation